1986
DOI: 10.1038/319507a0
|View full text |Cite
|
Sign up to set email alerts
|

Clonal origin of haematopoietic colonies in the postnatal mouse liver

Abstract: The liver of the neonatal mouse continues to show haematopoietic activity for up to 2 weeks after birth and morphological analysis has shown that this activity becomes focused in discrete haematopoietic colonies by the end of the first week postnatal. Furthermore, each colony contains cells of one haematopoietic lineage only, that is, erythroid, myeloid or pre-B-lymphoid cells. This pattern of differentiation suggests that each colony is derived from a single committed precursor cell, which, if true, would rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…The fetal hemopoietic liver as a source of myeloid precursor cells is well established [42], and fetal liver cells have successfully been used to restore granulopoiesis and monocytopoiesis in transplanted animals [43, 441. In addition, hemopoietic activity of the liver even up to 14 days of postnatal development has recently been reported to result in clonal hemopoietic foci and mixed colonies of erythroid cells and "Ma-like" accessory cells [45]. Infection of mice with oncogene-carrying retroviruses led to the establishment of leukemic, monocyte-like tumors in blood and liver.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The fetal hemopoietic liver as a source of myeloid precursor cells is well established [42], and fetal liver cells have successfully been used to restore granulopoiesis and monocytopoiesis in transplanted animals [43, 441. In addition, hemopoietic activity of the liver even up to 14 days of postnatal development has recently been reported to result in clonal hemopoietic foci and mixed colonies of erythroid cells and "Ma-like" accessory cells [45]. Infection of mice with oncogene-carrying retroviruses led to the establishment of leukemic, monocyte-like tumors in blood and liver.…”
Section: Discussionmentioning
confidence: 98%
“…Cells were incubated either in medium alone or with F4/80 mAb for 45 (15 x lo6 in 0.5 ml RPMI 1640) 2 h after irradiation. When indicated the mice received 500 pg pyran copolymer together with the cell suspension.…”
Section: Staining and Flow Cytometry Analysismentioning
confidence: 99%
“…In this way, 'oligoclones' would develop around individual macrophages before their exit into the circulation. Experimental evidence for this possibility has been obtained in studies of postnatal liver, using mouse chimeras (Rossant et al 1984), and has been inferred by the observation that erythroblasts often appear to be synchronized in erythroblastic islets isolated from regenerating adult haematopoietic tissues and foetal liver (Bessis et al 1978;Morris et al 1988). Similarly, with the mouse thymus, Kyewski & coworkers (1982) demonstrated that 'rosettes' of thymocytes attached to a central macrophage could be isolated by enzymic dispersion.…”
Section: Characterization Of Haematopoietic Cell Clustersmentioning
confidence: 96%
“…Alternate sections were hybridized with biotin-labelled nick-translated plasmids containing 1400 bp of the M. musculus major satellite DNA sequence (C. Davis, unpublished data) or a 900 bp fragment of the M. caroli major satellite sequence (G. Fraser & J. Rossant, unpublished data). Conditions of hybridization were essentially as previously described (Rossant et al 1986). Hybridization was visualized by binding of streptavidin-biotin-horseradish peroxidase complex (Enzo Biochem) to the biotinylated DNA.…”
Section: Methodsmentioning
confidence: 99%